Chapter British Socialism in the late 19th Century and the Question of Empire: John Ruskin and William Morris - Zinkiewicz, Grzegorz (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The paper explores contradictory approaches of late 19th century British socialists towards the legitimacy of the British Empire. As an illustration, two prominent socialist agitators of the Victorian era, John Ruskin and William Morris, have been selected. The central problem concerns the possible reasons for the radically different perceptions of the same formation by the Victorian sages who otherwise shared similar views on art and society; namely Ruskin’s apotheosis and Morris’ negation. At the same time, the text casts doubt on the popular belief that Ruskin took a shortcut in the face of growing uncertainty about the plausibility of his aesthetic theory, while Morris’ rejection of the Empire resulted from his programmatic anti-imperialism in accordance with the Marxist doctrine. The answer may actually lie in their former art-informed views and enterprises.